Heart transplantation in muscular dystrophy: Single‐center analysis. Issue 6 (21st March 2022) - Visrodia, Parth; Patel, Nikhil J; Burford, Matthew; Hamilton, Michele A.; Patel, Jignesh K.; Kobashigawa, Jon A.; Kittleson, Michelle M.
Abstract: Introduction: Cardiac involvement may occur in many forms of muscular dystrophy (MD). While cardiac disease may progress to warrant heart transplantation (HTx), there may be contraindications related to extra‐cardiac disease including pulmonary and skeletal muscle involvement that limit overall survival and impairs post‐transplant rehabilitation efforts. This study describes the MD HTx experience at a single high‐volume center. Methods: We examined the clinical characteristics and outcomes of patients with MD with heart failure (HF) ( n  = 28), patients with MD status post HTx ( n  = 20) and non‐MD HTx control group ( n  = 40) matched 2:1 for age at transplant, sex, listing status, and antibody sensitization. Results: Patients with MD who underwent HTx had increased ventilator days (2 vs. 1 days, p  = .013), increased hospital length of stay (20 vs. 12 days, p  = .022), and increased discharge to inpatient rehab (60% vs. 8%, p  < .001). By 1 year post HTx, patients with MD more often required assistive devices for walking (55% vs. 10%, p  = .01). Nonetheless, post‐HTx survival was similar at 1 year (100% vs. 97.5%, p  = .48) and 5 years (95.0% vs. 87.5%, p  = .36). Of the HTx recipients with MD, 95% were followed by a neurologist, 60% by a neuromuscular specialist as part of the Muscular Dystrophy Association Clinic at our center. Conclusion: Transplantation is a feasible option for patients with MD and advanced HF. MD patients who undergo transplantation may benefit from multidisciplinary specialized care to optimize MD‐related morbidity.